PENGARUH FIRM SIZE, UKURAN KANTOR AKUNTAN PUBLIK (KAP), PROFITABILITAS, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG YANG DIMODERASI DENGAN SPESIALISASI AUDITOR - Nasution, Siska Angreyani; Trisnawati, Rina (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of firm size, KAP size, profitability, and audit opinion on audit report lag which is moderated by auditor specialization in manufacturing companies listed on the Indonesian stock exchange for the 2018-2022 period. This research uses quantitative research, with a population of 225 companies listed on the Indonesian stock exchange in 2018-2022. The sampling method used in this research was purposive sampling. The total sample was 150 companies with 562 data analyzed. The analysis method uses Moderated Regression Analysis (MRA). The results of the analysis show that firm size and profitability have an influence on audit report lag. Meanwhile, KAP size, audit opinion has no influence on audit report lag in Manufacturing Companies listed on the Indonesian Stock Exchange in 2018-2022. And auditor specialization is unable to moderate the variables firm size, KAP size, profitability, and audit opinion regarding audit report lag in manufacturing companies listed on the Indonesian stock exchange in 2018-2022.